(untitled) (Praxis Educativa, 2012)
The Post-degree Title in Socio-Institutional Analysis and Animation, designed and coordinated by Lic. Lidia Fernandez, intended to form professors from Institutes of Teaching so that they became “extensionists”. The curricular design placed its emphasis on the work in intensive resi-dential laboratories. The “forced co-existence”, the accumulation of intensive working hours throughout the week, as well as the “intensity” of the time shared as a result of the high degree of personal involvement required by the task, allowed for the appearance and analysis of peculiar phenomena that produced formative effects of high interest. In the first part, I focused on the formative effects that these phenomena had had on the participants. In this second part, however, I am going to center the analysis on the impact of the same phenomena on the dy-namics of the coordinating team and on the conditions required for the perfor-mance of this task.